Induction of estrus in thyroidectomized-ovariectomized, nonlactating, Holstein cows - R.E. Stewart; M.O. Mee; I. Rettmer; Jeffrey S. Stevenson (Kansas Agricultural Experiment Station Research Reports, 1992)
Low thyroid activity (hypothyroidism) has been reported to decrease sexual behavior associated with reproduction in several species. Using estradiol benzoate (EB) and progesterone (P ), we attempted to induce 4 estrus in hypothyroid cows. Thyroid glands (thyroidectomy) and ovaries (ovariectomy) were removed surgically from nonlactating and nonpregnant Holstein cows that were culled from the Kansas State University dairy herd. Eight cows were thyroidectomized and ovariectomized (THYOVEX) and another four cows were ovariectomized only (OVEX). Starting 9 hr after injection of EB, cows were continuously observed for estrus for 36 hr. Frequencies of mounting activity and standing behavior were recorded for each cow. The percentage showing standing estrus was greater in cows that had no thyroid glands or ovaries than in cows without ovaries (78 vs 31%). Manifestation of estrus was identical in cows treated with EB or EB+P (62%). Interval from 4 EB injection to onset of standing estrus, frequency of mounting activity, and duration of standing estrus were similar among treatment groups and unaffected by the type of hormonal treatment. Thyroidectomized cows can exhibit estrous behavior, which is similar to that in ovariectomized cows treated with EB or P +EB.; Dairy Day, 1992, Kansas State University, Manhattan, KS, 1992;
Keywords: Dairy Day; 1992; Kansas Agricultural Experiment Station contribution; no. 93-131-S; Thyroidectomy; Overiectomy; Estrous behavior; Cattle